Development of A Simulation Package of Natural Gas Liquefaction System - Nur Shadrina Amalina; Thomas Milano Setiawan; Wisnu Hendradjit; Sutanto Hadisupadmo (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2017)
AbstractGas liquefaction employs refrigeration process to bring feed gas temperature down to enable it to condense. The refrigeration system for natural gas liquefaction consists of some components combined in several configurations. One of those systems is the reversed-Brayton and its modified cycles. A numerical program package was developed to model and analyze the process of natural gas liquefaction with maximum flow rate 31.7 kg/s. The package was set for the simple 1-stage reversed Brayton cycle and its modified cycle. The process was modelled with assumptions of a steady state condition and natural gas that made of 100% methane. Parameters and variables that may be involved in the simulation are the feed gas flow rate, temperature and pressure, the selection of refrigerants for the cycle, the refrigeration working pressures. The package enable one to calculate the amount of work required for liquefaction process as well as the system's performance in term of its figure of merit.